2016
DOI: 10.1002/jssc.201600864
|View full text |Cite
|
Sign up to set email alerts
|

Determination of benzo[a]pyrene in edible oils using phase‐transfer‐catalyst‐assisted saponification and supramolecular solvent microextraction coupled to HPLC with fluorescence detection

Abstract: For the analysis of edible oils, saponification is well known as a useful method for eliminating oil matrices. The conventional approach is conducted with alcoholic alkali; it consumes a large volume of organic solvents and impedes the retrieval of analytes by microextraction. In this study, a low-organic-solvent-consuming method has been developed for the analysis of benzo[a]pyrene in edible oils by high-performance liquid chromatography with fluorescence detection. Sample treatment involves aqueous alkaline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Saponification is an effective method for eliminating these compounds from the sample matrix. Typically, edible oil samples are treated with a methanol KOH (e.g., 4 mol/L) solution, followed by two to three extractions with hexane or toluene [ 21 ]. Of course, KOH solution can be replaced with other alkalis, such as NaOH solution.…”
Section: Sample Preparation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Saponification is an effective method for eliminating these compounds from the sample matrix. Typically, edible oil samples are treated with a methanol KOH (e.g., 4 mol/L) solution, followed by two to three extractions with hexane or toluene [ 21 ]. Of course, KOH solution can be replaced with other alkalis, such as NaOH solution.…”
Section: Sample Preparation Methodsmentioning
confidence: 99%
“…Of course, KOH solution can be replaced with other alkalis, such as NaOH solution. Through experiments, Wang et al [ 21 ] found that, when using 4 mol/L, 6 mol/L, and 8 mol/L KOH for saponification reactions as pre-treatments for edible oils, the recovery rates of BaP (benzo[a]pyrene) could reach 94%, 93%, and 91%, respectively. However, the alkali used in the saponification process is generally dissolved in an organic solvent like methanol [ 22 ].…”
Section: Sample Preparation Methodsmentioning
confidence: 99%